Intraparticle convection, diffusion and reaction of substrate in porous slab catalysts for zero order reaction - Fakih, Syibli Milasi; Jameel, Ahmad Tariq; Noor Batcha, Ibrahim Ali (Faculty of Engineering, International Islamic University Malaysia (IIUM), 53100 Kuala Lumpur Malaysia, 2012)
Diffusion-reaction problem in a porous solid catalyst is important in the design and analysis of heterogeneous phase reactors and has been extensively studies. However, the effect of intraparticle convection on the substrate transport inside the solid has been scantly reported in the literature, though intraparticle convection plays significant role in enhancing the substrate transport inside the porous catalyst. This becomes more significant especially in the case of immobilized biocatalysts applications with limited reactant solubility, such as oxygen in aqueous phase, typically encountered in aerobic fermentation and biodegradation. Though earlier works have reported on the effect of intraparticle convection on the nutrient transport in porous solid catalysts, there remain gaps and unexplored aspects of this problem. This research investigates the effect of intraparticle convection for the case of zero order reaction in slab geometry. The convection effect is represented in term of intraparticle Peclet Number in the differential equation obtained as a result of mass balance for the nutrient transport inside the solid catalyst. The effect of intraparticle flow on the intrapraticle nutrient transport is studied by solving the resulting differential equation for the concentration profile inside the solid which in turn is used to calculate the effectiveness factor of the catalyst. The exact solutions for the zero order reactions is obtained following the analytical approach. The numerical solution using an explicit finite difference scheme is used to validate our analytical results. The analytical and the numerical solutions almost superimpose each other which proves that our analytical solution is correct. The results show that the convection enhances the rate of nutrients transport inside the porous solid. With the increasing value of Intraparticle Peclet Number, the substrate penetrates deeper into the solid in the direction of the flow.